An in vitro study of oncogenesis of primary cervical cells by human papillomavirus 16 and cigarette smoke condensate - Yang, Xiaolong, 1964- (1995)
Thesis (M.Sc.)--Memorial University of Newfoundland. Medicine Bibliography: leaves 176-205. In process